Analysis of Creative Thinking Ability Judging from the Confidence of Class XI Students of SMA Negeri 1 Bambanglipuro - Wahyu Septina Anggraini; Vita Istihapsari (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
Abstract The purpose of this study was to describe the creative thinking ability of class XI students of SMA Negeri 1 Bambanglipuro in terms of high, medium and low levels of confidence in the material of sequences and series. This research is a descriptive qualitative research. The subjects of this study were 6 students of class XI IPS 1 at SMA Negeri 1 Bambanglipuro with high, medium and low levels of self-confidence. Data collection techniques used in this study were questionnaires, tests and interviews, then the data obtained were analyzed using data triangulation techniques. This study resulted that subjects with a high level of self-confidence at TKBK 4 (very creative) were able to meet all aspects of creative thinking indicators, namely, fluency, flexibility and novelty and being at TKBK 3 (creative) were able to meet the indicators of creative thinking, namely fluency and flexibility. Subjects with a moderate level of self-confidence at TKBK 3 (creative) were able to meet the creative thinking indicators, namely fluency and flexibility. Meanwhile, subjects with low self-confidence were at TKBK 2 (creative enough) were able to meet the flexibility creative thinking indicator and were at TKBK 1 (less creative) were able to meet the creative thinking indicator, namely fluency. Keywords: Creative Thinking Ability, Self Confidence, Lines and Series